Implementasi Program Pembiasaan Membaca Al-Qur’an sebelum Kegiatan Belajar Mengajar (KBM) di MTSN 1 Padang Lawas - Nasution, Sinar; Rahman, Abd (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to determine the implementation of the Al-Qur'an reading habituation program before teaching and learning activities (KBM) at MTSN 1 Padang Lawas. MTSN 1 Padang Lawas is one of the madrasas that carries out the habit of reading the Al-Qur'an for 15 minutes before learning begins, which is guided and led by the first tutor. This type of research is qualitative with a descriptive approach. This research was carried out by looking at ongoing events and processes. The data source was taken directly from the first data source, namely the Madrasah Head, Religion Teacher, Subject Teacher, and Students. The results of this research are the steps in implementing the Al-Qur’an reading habituation program at MTSN 1 Padang Lawas, starting from reading in turns between one student and another according to the teacher's instructions, then listening and listening directly by the teacher, after that it is understood together, evaluation and providing motivation from the teacher. Apart from that, supporting and inhibiting factors for this program were also found. Supporting factors for this program are the availability of the Al-Qur’an, student interest, conducive classes and motivation. The inhibiting factors are the lack of time allocation and the background of each student which causes their reading abilities to be unequal.